Evaluation of Crop Water Status and Vegetation Dynamics For Alternate Partial Root-Zone Drip Irrigation of Alfalfa: Observation With an UAV Thermal Infrared Imagery - Lu, Saihong; Zhang, Tong; Tian, Fei (Frontiers in Environmental Science, 2022)
Characterization of the spatiotemporal patterns of crop water status and vegetation dynamics are a prerequisite to overcome water scarcity and obtain precise agricultural water management. Based on high-resolution aerial thermal imagery, we estimated crop water stress index (CWSI), transpiration rate (T), and crop growth status. The research was conducted with conventional subsurface drip irrigation (abbreviated as R) and alternate partial root-zone drip irrigation (abbreviated as P) under four different irrigation quotas: 0 mm, 10 mm, 20 mm, and 30 mm, which are denoted as CK, R10 (P10), R20 (P20), and R30 (P30), respectively. Results indicate that the CWSI is a suitable tool to define alfalfa water status under different irrigation regimes. The CWSI values reflect CK > R10 > R20 > P10 > P20 > R30 > P30, with values of 0.57, 0.41, 0.26, 0.24, 0.18, 0.17, and 0.13, respectively. The T values show that CK < R10 < P10 < R20 < P20 < R30 < P30, with values of 0.46 mm/h, 0.61 mm/h, 0.70 mm/h, 0.71 mm/h, 0.76 mm/h, 0.77 mm/h, and 0.78 mm/h, respectively. In addition, under the same irrigation quotas, the CWSI presented as P10, P20, and P30 was lower than R10, R20, and R30, respectively, while the T was the opposite. Taking the improved transpiration rate as the amount of water saving, it was demonstrated that the alternate partial root-zone drip irrigation was a water-saving method, and each increase of 10 mm in alternating irrigation quotas could save 67.2, 18.4, and 4.6% of water, respectively. This evaluation contributes to a better understanding of the spatiotemporal variations of water and growth status and provides references and theories for the development of modern precise agriculture.